2019
DOI: 10.14740/cr888
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab-Induced Cardiomyopathy and Intermittent Left Bundle Branch Block

Abstract: Trastuzumab-induced cardiomyopathy is a known complication of its use in breast cancer treatment, but it remains mostly asymptomatic and often reversible. Non-myopathic cardiac complications have been rarely reported with trastuzumab. These include left and right bundle branch block, arrhythmias and sinus node dysfunction. We report a case of a 52-year-old female breast cancer patient with trastuzumab-induced asymptomatic intermittent left bundle branch block recurring nearly a year after the initial diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…New onset LBBB has not been commonly reported in chemotherapy‐related cardiac dysfunction. While 44% of patients with CHIC and LBBB in our study had progression from non‐specific intraventricular conduction delay to LBBB after being exposed to chemotherapy, only a few cases in the literature have described new onset LBBB with cancer‐directed therapy, particularly with trastuzumab and rituximab 5–8 …”
Section: Discussionmentioning
confidence: 57%
“…New onset LBBB has not been commonly reported in chemotherapy‐related cardiac dysfunction. While 44% of patients with CHIC and LBBB in our study had progression from non‐specific intraventricular conduction delay to LBBB after being exposed to chemotherapy, only a few cases in the literature have described new onset LBBB with cancer‐directed therapy, particularly with trastuzumab and rituximab 5–8 …”
Section: Discussionmentioning
confidence: 57%
“…In a larger study including 68,113 BC patients, the chemotherapy group was shown to have higher Af incidence, while in the subgroup analysis, there were no significant differences regarding trastuzumab use [29]. Other abnormal electrocardiogram findings, including branch bundle blocks, QT prolonged, ventricular bigeminy, and non-sustained ventricular tachycardia in HER2-expressed BC patients, were shown as case reports [30][31][32]. A small cohort of 20 metastatic HER2 BC patients reported no arrhythmias after trastuzumab infusion [33].…”
Section: Chang Et Al Revealed Trastuzumab-induced Risk Of Maccementioning
confidence: 96%
“…In a larger study including 68113 BC patients, the chemotherapy group was shown to have higher Af incidence, while in the subgroup analysis, there were no signi cant differences regarding trastuzumabuse [40]. Other abnormal electrocardiogram ndings, including branch bundle blocks, QT prolonged, ventricular bigeminy, and non-sustained ventricular tachycardia in HER2 expressed BC patients, were shown as case reports [41][42][43]. A small cohort of 20 metastatic HER2 BC patients reported no arrhythmias after trastuzumab infusion [44].…”
Section: Grazette Et Al Showed Mitochondrial Dysfunction In Rat Myocy...mentioning
confidence: 94%